Research on the Use of Hydro-Pneumatic Shock Absorbers for the Rear Suspension of a Vehicle Cabin - Vasile Gheorghe; Eliza Chircan; Horatiu Teodorescu Draghicescu (Applied Sciences, 2025)
This work explores enhancing rear cabin suspension in vehicles using hydro-pneumatic shock absorbers to maintain the cabin position regardless of load and improve safety by mitigating oscillation impacts. Advanced solutions employ pneumatic elastic elements with automatic adjustment, addressing classic suspension disadvantages like variable cab position and natural frequency with load changes. The experimental analysis of reinforced rubber samples from the air socket material involved tensile testing and scanning electron microscopy. The tensile results showed a clear trend: weak reinforced samples (L, T) were ductile but had a lower strength, while the ones on the reinforcing direction (D_45, D_60) exhibited a significantly increased strength and stiffness, with D_60 being the strongest but least ductile. Stress–strain curves visually confirmed these mechanical behaviors. Crucially, SEM images of fracture surfaces consistently revealed widespread fiber pull out. This indicates that weak interfacial adhesion between the reinforcing fibers and the rubber matrix is a primary limiting factor for the composite′s overall strength.